Calculation of electric field and temperature distribution within a microwave oven with realistic geometric features geometric features using numeric simulations. Issue 1 (2nd January 2021) - Yi, Zhengkai; Qiu, Weiqiang; Jiao, Yang; Row, Kyung Ho; Cheng, Yu-dong; Jin, Yinzhe
Abstract: Many simulations employed in microwave heating simplify the geometric model of the microwave cavity to reduce the complexity of the model. Some detailed design features of the cavity, such as magnetron and cavity depression, are usually ignored. This study built detailed geometric models (DGM) and simplified geometric models (SGM) to investigate the changes in the electric field in a microwave cavity. A three-dimensional finite element model was developed to simulate rotating and stationary food (mashed potatoes) during microwave heating, and the simulation parameters and strategy during rotation were optimized. The simulations using DGM and SGM were compared by comparing the simulated transient temperature profiles and spatial temperature patterns with physical experiments. The results indicate that the temperature patterns of the DGM differed significantly from the SGM, and the simulation results of the DGM were closer to the experimental results. The presence of the magnetron, plastic bearing and detailed glass turntable had little influence on the electric field, but the dents had the great influence. The influence of dents on the heating uniformity was discussed in detail.